Learning by Doing in Architectural Education: From Urban Design to Architectural Design, Yenikapi-Inebey Case Study - Erkan Yazıcı, Yasemin; TÖRE, EVRİM ÖZKAN (Turkish Education Assoc, Kızılırmak Caddesi No 8, Kocatepe, Ankara 00000, Turkey, 2014)
This paper reports a 2 semester study conducted with 74 undergraduate students of Architecture at the Istanbul Kultur University to investigate the extent of architectural design students' use of urban design information in their projects by learning by doing method. In the first semester, students performed a comprehensive analysis of the Yenikapi-Inebey Quarter of Istanbul in terms of urban design criteria. In the second semester, students were given the task of creating a massing study of an architectural design project which was not constrained in terms of function, hmax or building coefficient, near the project site. This was followed by an open ended question to identify the criteria which influenced the designs of the students. The results of the research reveal that, in terms of learning by doing method, the students are competent to carry the knowledge and aspects of urban design to the lower scales of design.
Keywords: Design education; Learning by doing; Urban design; Architectural design; Yenikapı